Contamination of Heavy Metals (Pb and Cu) at Tin Sea Mining Field and Its Impact to Marine Tourism and Fisheries - Sudirman Adibrata; Muh. Yusuf; Irvani Irvani; Maulana Firdaus (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
The dynamics of heavy metals (Pb and Cu) distribution near sea mining locations can show a negative impact on fisheries resource management. The study was conducted at the coastal area of Tanah Merah Beach, Central Bangka Regency, the geographical location at 02o12'50 "S and 106o13'00" E. This study aims to determine the extent of heavy metals (Pb and Cu) distribution adjacent sea mining field and its impact on marine tourism and fisheries. Purposive sampling method was used to identify the sampling locations from 13 closest locations to the farthest from marine mining sources. The result show that the closest and farthest Pb and Cu values from the tin mining activities were 0.16 mg.L-1; 0.03 mg.L-1 and 0.02 mg.L-1; <0.003 mg.L-1. The Hydro-oceanographic conditions from the highest to the lowest water currents of 0.03 m.s-1 - 0.001 m.s-1. This research represented the east monsoon, which showed that the heavy metal distributions dynamics are not too distance-reaching due to weak water currents, so that the dilution and sedimentation rate is slow. It is stated that the waters are polluted where the highest contamination value is indicated by the location closest to the source of marine mining and further weakened at the location farthest from the source of pollutants. Environmental impact from that activity has significantly threatened marine tourism and fishery activities by reducing economic benefits that given from marine and coastal environmental. Urgently, it is necessary to regulate like zoning tin mining activities and sites for the sustainable common purposes and prevent conflicts.